Demand feeding system for juveniles of groupers, brown-marbled grouper and orange-spotted grouper - Mukai, Yukinori; Tan, Nai Han; Mohammad Seth, Siti Nasihin; Firdaus, Rian Freddie; Chung , Fan Liau (2013)

(untitled)
Demand feeding is a new feeding method by which fish can feed themselves. Fish switch on the feeding device when they require food. This method has several advantages because the fish can eat when they are most motivated to feed. The system can thus minimize feed loss and reduce water pollution. The demand feeding system has been studied for ten years, but so far, there are only a few commercialized feeding devices. Currently, the most urgent issue facing the aquaculture industry in Malaysia is seed production, especially, groupers. This study was conducted to examine juvenile rearing by demand feeding system with brown-marbled grouper Epinephelus fuscoguttatus and orange-spotted grouper, Epinephelus coioides. 10 juveniles were kept in a 500 L round polyethylene tank (nine tanks, 90 fish). The tanks had water running system with water change (90%) every morning. Throughout the experiment, fish were exposed to natural photoperiod. Water temperature was 26.5 – 30.5 °C and salinity was 26-29 ppt. During rearing experiment, the fish were fed with pellets (Otohime EP3, Marubeni Nisshin Feed Co. Ltd.). Three experimental groups, pendulum demand feeder group (PDF, FH221, Aquatic Eco-Systems, Inc.), infrared sensor demand feeder group (IRDF) and automatic feeder group (AF) were set with three replicates. The IRDF consisted of an infrared sensor (infrared light 860 nm) ending in a red pellet-like knob with food container. Both demand feeders (PDF and IRDF) were set to dispense 10-15 pellets when fish activated the trigger (pendulum rod and infrared sensor respectively) located 2 cm below the water surface. The automatic feeder (AF) was set to dispense 130-150 pellets at 08:00 and 17:00 h. The experiment lasted for 20 days. Fish growth rates; total length (TL) and body weight (BW) were compared. Fish growth of three experimental groups of each grouper was obtained. In the experiment of brown marbled grouper, total length of IRDF group was higher than that of PDF group (P<0.05). BW growth rates of three groups were not significant different. In the experiment of orange-spotted, there are no significant differences, but TL and BW growth rates of IRDF group showed higher tendency than that of AF and PDF groups. Therefore, IRDF demand feeding devises are suitable for juvenile rearing of groupers.